2015
DOI: 10.1080/02699931.2015.1049937
|View full text |Cite
|
Sign up to set email alerts
|

Reappraisal mitigates overestimation of remembered pain in anxious individuals

Abstract: Anxiety sensitivity, a trait characterised by fear of anxiety-related body sensations, has been linked to heightened attention to pain, appraising body sensations as threatening, and remembering threatrelated information. We assessed whether individuals with greater anxiety sensitivity overestimate in remembering pain. We also assessed whether emotion regulation strategies that direct attention away from pain (distraction), or alter appraisals of pain (reappraisal), alleviate memory bias. Participants (N = 137… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…Only a limited number of studies have involved experimental manipulation of current appraisals with memory of emotion as the outcome measure (e.g., Keuler & Safer, 1998;Safer, Levine, & Drapalski, 2002;Hovasapian & Levine, 2016). In what they called "the first controlled experiment to investigate memory of emotions," Keuler and Safer (1998;p.…”
Section: Experimental Research On the Malleability Of Memory Of Emotionmentioning
confidence: 99%
“…Only a limited number of studies have involved experimental manipulation of current appraisals with memory of emotion as the outcome measure (e.g., Keuler & Safer, 1998;Safer, Levine, & Drapalski, 2002;Hovasapian & Levine, 2016). In what they called "the first controlled experiment to investigate memory of emotions," Keuler and Safer (1998;p.…”
Section: Experimental Research On the Malleability Of Memory Of Emotionmentioning
confidence: 99%
“…Down-regulating painful sensory experiences via reappraisal mitigated overestimation of remembered pain in anxious individuals (Hovasapian & Levine, 2016), reduced facial expression of pain (Hampton et al, 2015), and increased pain tolerance (Jokic-Begic et al, 2009). It also was associated with attenuation of self-reported indices of pain (Fardo et al, 2015;Hampton et al, 2015;Lapate et al, 2012), although inconsistently (Jokic-Begic et al, 2009), as well as modulation of heart rate Lapate et al, 2012), corrugator electromyography responses (Lapate et al, 2012), and neuroendocrine activity (Benedetti et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…Thus, another line of research introduced an alternative approach: promoting participants' active involvement in achieving a self-regulatory goal. To do so, some studies used positive self-statements, e.g., "I can stand this" (Jokic-Begic, Ivanec, & Markanovic, 2009); some involved reinterpretation of sensory experiences, e.g., imagining thermal stimulation as a hot bath (Fardo, Allen, Jegindø, Angrilli, & Roepstorff, 2015;Hampton, Hadjistavropoulos, Gagnon, Williams, & Clark, 2015;Lapate et al, 2012;Woo, Roy, Buhle, & Wager, 2015); some used verbal suggestions, e.g., convincing subjects that a procedure would improve their health (Benedetti, Thoen, Blanchard, Vighetti, & Arduino, 2013;Hovasapian & Levine, 2016); others combined some of the aforementioned methods (Denson, Creswell, Terides, & Blundell, 2014;Kalisch et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The memory of pain is consistently regarded as an important topic for research (Erskine et al., ; Niven and Murphy‐Black, ; von Baeyer et al., ; Noel et al., ). Although several studies have shown that pain may be remembered accurately (Lefebvre and Keefe, ; Bąbel, , , ; Hovasapian and Levine, ), there is also evidence indicating that people tend to overestimate (Gedney and Logan, , ; Broderick et al., ; McNeil et al., ) or underestimate it (Fors and Götestam, ; Eli et al., ; Rode et al., ; De Pascalis et al., ; Bąbel, ). Such inconsistency in the research findings inspires the search for the factors influencing the accuracy of remembering pain.…”
Section: Introductionmentioning
confidence: 99%